Angiotensin‐(1‐7) Prevents Angiotensin II‐induced Fibrosis in Cremaster Microvessels. (January 2015) - Carver, Kyle A.; Smith, Thomas L.; Gallagher, Patricia E.; Tallant, E. Ann
Abstract Objective The effect of the heptapeptide hormone Ang‐(1‐7) on microvascular fibrosis in rats with Ang II‐induced hypertension was investigated, since vascular fibrosis/remodeling plays a prominent role in hypertension‐induced end‐organ damage and Ang‐(1‐7) inhibits vascular growth and fibrosis. Methods Fibrosis of cremaster microvessels was studied in male Lewis rats infused with Ang II and/or Ang‐(1‐7). Results Ang II elevated systolic blood pressure by approximately 40 mmHg, while blood pressure was not changed by Ang‐(1‐7). Ang II increased perivascular fibrosis surrounding 20–50 μm arterioles as well as interstitial fibrosis; coadministration of Ang‐(1‐7) prevented the increases in fibrosis. The fibrotic factor CTGF and phospho‐Smad 2/3, which upregulates CTGF, were increased by Ang II; this effect was prevented by coadministration of Ang‐(1‐7). Although TGF‐β phosphorylates Smad 2/3, TGF‐β was no different among treatment groups. In contrast, Ang II increased the MAP kinase phospho‐ERK1/2, which also phosphorylates Smad; p‐ERK was reduced by Ang‐(1‐7). Ang‐(1‐7), in the presence or absence of Ang II, upregulated the MAP kinase phosphatase DUSP1. Conclusions These results suggest that Ang‐(1‐7) increases DUSP1 to reduce MAP kinase/Smad/CTGF signaling and decrease fibrosis in resistance arterioles, to attenuate end‐organ damage associated with chronic hypertension.